The Concept of Educators in Islam: An Integrative Study of the Quran and Hadith on Ethics and Virtue - Yolanda Septiani; Maspuroh; Siti Ajijah; M. Agung Febriansyah; Nessa Sri Neda; M. Syukron (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
The study of various ways of delivering educational material can be traced back to sources of Islamic law, known as the Al-Quran and Hadist views on the object of education. The urgency of this research is to prove that the Al-Quran dan Hadist provides important insights not only for people who are knowledgeable, but also want to put their knowledge into practice. It is said to be an Overview of the Al-Quran because the study of this method does not necessarily follow the pronunciation of the tariqah in the Al-Quran, but rather verses without the pronunciation of the tariqah but the meaning contains an educational pronunciation. This research uses qualitative research methods with inductive document analysis techniques. The results of this research show that becoming an educator is not easy, there are several characteristics that are requirements for becoming an educator. However, Allah and Rasulullah greatly prioritized an educator. There are many promises from Allah in the Al-Quran and hadist about the glory of an educator, teacher, scholar, and people who want to put their knowledge into practice.